Modes of catheter insertion for peritoneal dialysis - Huang Si-yue; Liang Wei; Wang Hui-ming (Linchuang shenzangbing zazhi)
Peritoneal dialysis （PD） is an effective treatment forend-stage renal disease. The success of PD depends largely on a well-functioning peritoneal catheter.Selecting an appropriate mode of catheter insertion should be based upon patientstatus，operator technique，expenditure and other factors.